Complementary Split Ring Resonator based Sensor for Crack Detection - Rajni Rajni; Amanpreet Kaur; Anupma Marwaha (Institute of Advanced Engineering and Science, 2015)
In this paper, the performance of Complementary Split Ring Resonator(CSRR) based sensor is explored by varying the geometrical parameters of asub millimeter crack. Behavior analysis of the CSRR based sensor isperformed by variation in the parameters of crack. Variation in resonantfrequency of sensor is observed in every case and is noteworthy for ourpurpose. This signifies the sensor’s ability to detect crack of differentgeometrical parameters on a metal surface.The effectiveness of the sensor isbeing contemplated through this approach which is appreciable. Anillustrious performance of the crack detection sensor has been discovered inthis analysis. Simulated results show the feasibility of detecting very smallcracks upto 25 ????m width, in the metallic surfaces.